Patients' Health Related Quality of Life after Percutaneous Coronary Intervention i n Baghdad City. - Ayad Majid Mousa; Huda Baqer Hassan (Kufa Journal for Nursing Sciences)
Objectives: The study aims to assess the patients' health related quality of life and find out the association between the gender, age, marital status, educational level, employment, body mass index, severity of disease vessels, and number of implanted stents with health related quality of life.